2020
DOI: 10.3390/molecules25184298
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of αvβ5 Integrin in HepG2 Cell Line by RGDechi15D Peptide

Abstract: Recently, the research community has become increasingly concerned with the receptor αvβ5, a member of the well-known integrin family. Different ongoing studies have evidenced that αvβ5 integrin regulates not only physiological processes but also a wide array of pathological events, suggesting the receptor as a valuable biomarker to specifically target for therapeutic/diagnostic purposes. Remarkably, in some tumors the involvement of the receptor in cell proliferation, tumor dissemination and angiogenesis is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In addition, several preclinical trials have been ongoing in evaluating the therapeutic efficacy of integrin targeting in antitumor therapy. [49,[142][143][144][145][146] As integrins are expressed in various normal cells, their targeting should be critically evaluated for both acute and chronic toxicities.…”
Section: Clinical Trials In Integrin Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several preclinical trials have been ongoing in evaluating the therapeutic efficacy of integrin targeting in antitumor therapy. [49,[142][143][144][145][146] As integrins are expressed in various normal cells, their targeting should be critically evaluated for both acute and chronic toxicities.…”
Section: Clinical Trials In Integrin Targetingmentioning
confidence: 99%
“…Under normoxic and hypoxic conditions, T7 peptide inhibits endothelial cell proliferation, migration, and angiogenesis through the integrin α3β1 and αVβ3 pathways and promotes apoptosis of HCC endothelial cells. [ 142 ] Capasso et al [ 143 ] recently reported a cyclic peptide RGDechi15D that specifically binds to integrin αVβ5 and does not cross-react with integrin αVβ3. Here, they demonstrated that RGDechi15D can interfere with the PI3K pathway, inhibit HCC cell adhesion, proliferation, and invasion, and reduce HCC endothelial cell angiogenesis.…”
Section: Targeting Integrins As Hcc Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…RGDechi15D reduces cell adhesion, migration, invasion, angiogenesis and proliferation of cancer cells overexpressing α v β 5 . 91 …”
Section: Types Of Acps and Their Mode Of Actionmentioning
confidence: 99%
“…RGDechi15D reduces cell adhesion, migration, invasion, angiogenesis and proliferation of cancer cells overexpressing a v b 5 . 91 Recently, a peptide mediated imaging technique for glioblastoma cells was reported. Transformed cells in glioblastoma show high intracellular levels of reactive oxygen species (ROS) and various imaging probes target these high ROS levels.…”
Section: Anti-metastatic Peptides Targeting Integrinsmentioning
confidence: 99%